Phylogenetic and clonality analysis of bacillus pumilus isolates uncovered a highly heterogeneous population of different closely related species and clones - Branquinho, Raquel (2015)
Bacillus pumilus is a Gram-positive bacterium with a wide range of attributed applications, namely as a plant growth promoting rhizobacteria (PGPR), animal, and human probiotic. However, a rare putative role in human diseases has been reported, namely in food poisoning or as anthrax-like cutaneous infectious agent. This species is difficult to distinguish from its closely related species on the basis of phenotypic or biochemical characteristics and 16S rRNA gene sequences. In this study, the phylogenetic analysis of gyrB and rpoB gene sequences of a collection of isolates previously identified as B. pumilus, assigned most of them (93%, 38 of 41 isolates) to B. safensis or to the new recently described B. invictae. Moreover, we extended the previously reported recognized habitats of these species and unveiled a human health or biotechnological relevance (e.g. as implicated in food poisoning or PGPR) for them. Additionally, we demonstrated that both B. safensis and B. invictae species encompass a clonally diverse population, which can justify their great adaptation ability to different niches, with evidence of clonal-host specificity